Noncanonical Obligatory Control - Landau, Idan (Language and linguistics compass, 2024)
Intensive research on Obligatory Control (OC) in the past 2 decades has revealed a rich crosslinguistic terrain of deviations from the classical format. Five types of noncanonical OC are surveyed here: Finite control, controlled overt pronouns, partial control, proxy control and crossed control. Each one is described and illustrated, paying attention to methodological difficulties in establishing its characteristic empirical signature. We then turn to a critical assessment of leading theoretical accounts of these phenomena, pointing to merits and faults, and indicating how they can be integrated with broader concerns of syntactic theory.